UTILIZATION OF DIGITAL MARKETING FOR KACA CIPTA MANDIRI MSMES - Johny Budiman; Widia Agustiwi (ConCEPt - Conference on Community Engagement Project, 2022)
The purpose of this community dedication that was done by executor to Kaca Cipta Mandiri is increasing their customer by 10% and about 10% of minimum income by giving a solution and idea for the problems faced by the owner of business. The main problem faced by the owner is lack of knowledge incessantly by using social media and implement the digital marketing. Usually, the workshop only provides goods by direct selling and worth of mouth strategy so that the business hasn’t growing rapidly and public still don’t have any knowledge about the workshop. Data collection of practical work is using 2 methods, that is survey and interview to find out the business’s background and problems that the business is facing. And using observation method that was useful for concluding the problems and proving ideas using digital marketing using one of promotion mix, that is direct marketing. The media used are Instagram, Whatsapp Business, E-catalogue, and Linktree Website. The result of implementing digital marketing is the availability of social media accounts such as Instagram, Whatsapp Business, E-catalogue and Linktree Website under Kaca Cipta Mandiri’s business name. The implement done created selling record for up to 5% and selling income for about 5% based on inquires over whatsapp business and suggestion for the next student creativity program is the usage of digital marketing that is currently being implemented can be added with more the latest various marketing systems.